Antimicrobial and Antioxidant Activity Screening of Mushrooms Growing in the Leningrad Region - A. K. Whaley; A. O. Whaley; V. V. Novikova; V. O. Vasiliev; A. V. Klemper; R. I. Lukashov; N. I. Mandrik; N. S. Gurina; G. P. Yakovlev; V. G. Luzhanin (Разработка и регистрация лекарственных средств, 2023)
Introduction. The emergence of new strains of microorganisms that are multidrug resistant (MDR) in relation to the antimicrobial drugs used is one of the pressing problems of modern medicine. To prevent an increase in MDR-related deaths, the search for new antibiotics and their introduction into medical practice must be continuously ongoing. Infectious diseases are also accompanied by cell damage and the development of free radical oxidation processes, therefore the search for new antioxidants is also an important task. Considering the powerful biosynthetic potential of basidiomycetes, this group of fungi has every prospect of becoming a new source of biologically active substances in general, as well as antibiotics and antioxidants in particular. Cap mushrooms, represented mainly by basidiomycetes, number about 14,000 species and are an accessible source of raw materials for the search for promising antimicrobial compounds and antioxidants.Aim. Study of the antioxidant and antimicrobial activity of total extracts obtained from cap mushrooms against Escherichia coli, Staphylococcus aureus and Candida albicans and assessment of the suitability of cap mushrooms as a natural source of substances with antimicrobial and antioxidant activity.Materials and methods. The antifungal and antibacterial activity of the extracts was determined by the micromethod of two-fold serial dilutions in a liquid nutrient medium in 96-well plates in duplicate. The study of this type of biological activity was carried out against reference (type) strains Staphylococcus aureus ATCC 6538-P, Escherichia coli ATCC 25922, Candida albicans NCTC 885-653. To study antioxidant activity using DPPH, we used alcoholic extracts from the fruiting bodies of mushrooms obtained by maceration with 96 % ethanol at a ratio of raw materials to extractant of 1 to 8 for 24 hours, an aqueous solution of ascorbic acid (vitamin C) and an ethanol solution of Trolox.Result and discussion. In relation to S. aureus, a representative of gram-positive flora, the studied extracts of cap mushrooms showed low activity, on average about 2500 or 5000 μg/ml. In relation to E. coli, a representative of gram-negative flora, 8 % of the studied cap mushroom extracts showed an average activity of about 1250 μg/ml. The largest number of cap mushroom extracts – 19% of all studied species – showed activity against the yeast micromycete C. albicans. The highest activity against C. albicans was observed in extracts of the mushrooms Cantharellula umbonata with an MIC of 625 μg/ml, Cortinarius olivaceofuscus with an MIC of 625 μg/ml, and Hypomyces chrysospermus with an MIC of 312 μg/ml. During screening of antioxidant activity, the studied extracts were divided into three groups: with high (more than 50 % PPR), medium (from 15 to 50 % PPR) and low (less than 15 %) antioxidant activity. It was shown that the sum of phenolic compounds significantly correlates with the level of antioxidant activity in all three groups, but in the groups with medium and low antioxidant activity there are also other non-phenolic groups of compounds that make a significant contribution to the total antioxidant activity.Conclusion. Cap mushrooms are a promising source of biologically active substances with antifungal and antioxidant activity.